“BORDER” AS A PHILOSOPHICAL CATEGORY - DEMIRTSHYAN, MOVSES (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
The article is devoted to the study of the meaning of the concept “border” in the social and humanitarian studies. It is difficult to imagine a complete modern study of any field or area of social life that is not related to the phenomenon of border, its features, and significance in one way or another. The article argues, that for a long time in the history of philosophy the border has not been considered as a separate and unique “space”, but as a dividing line, beyond which a phenomenon turns into its opposition (existence and non-existence, knowledge and ignorance, etc.). M. Bakhtin’s new understanding of the border showed, that the emergence of new meanings and values in culture is connected not only with the evolutionary development of the culture but also with the dialogue with other cultures, which takes place at a time when two or more cultures meet at the border. The border in philosophical-cultural studies has gained the status of a meaningful fact, as it has been substantiated that subjects on both sides of the border (cultures, societies, epochs, specific people, etc.) discover previously unknown, hidden meanings, values, and perspectives through dialogue. This is due to the fact that the dialogue in the border situation is carried out by answering “Other’s” questions. This process can be presented in the following formula: "Only by answering the “you” addressed to me, I become “I”. It is obvious that this is directly related to one of the central issues of social philosophy, which is identity and implies a new interpretation of it. The border in the social and humanitarian research has gone through several stages of understanding, considered as a physical border, and then as a symbolic and ritual phenomenon, and then as a text. The article shows that the border performs the functions of a “border guard” and “filter” in all forms, preserving the individuality of the culture and ensuring the reproduction of identity. It is most evident in the revival of national cultures under the influence of modern globalization, which is exactly a process of restoring or strengthening endangered cultural boundaries.
Keywords: border, measure, dialogue, opposition, culture, ritual, symbol, text, communication, identity